2015
DOI: 10.11604/pamj.2015.20.201.5996
|View full text |Cite
|
Sign up to set email alerts
|

Apport de la tomodensitométrie dans le diagnostic de la tuberculose vertébrale à propos de 496 cas à Abidjan

Abstract: IntroductionLe mal de Pott est la forme la plus fréquente des tuberculoses ostéo articulaires, le diagnostic de certitude reste difficile. L'imagerie tient une place indéniable dans le diagnostic. L'objectif de cette étude était de déterminer la prévalence de la tuberculose vertébrale et l'apport de la TDM dans le diagnostic.MéthodesNous avons mené une étude rétrospective sur dossiers de tuberculose vertébrale dans le service de Rhumatologie du CHU de Cocody de Janvier 2006 à Décembre 2013. N'ont pas été inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
(13 reference statements)
3
5
0
Order By: Relevance
“…The average age of our patients at the time of diagnosis was 47.5 years, which was similar to other studies conducted in Africa that reported age of adult patients with musculoskeletal TB ranging from 40 to 60 years [7, 911]. A slight male predominance of the disease has often been reported in the literature [8, 12]. As noted by other authors, patients with spinal TB were of lower social class [8, 13], and many of them did not present earlier with signs of pulmonary TB [10].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The average age of our patients at the time of diagnosis was 47.5 years, which was similar to other studies conducted in Africa that reported age of adult patients with musculoskeletal TB ranging from 40 to 60 years [7, 911]. A slight male predominance of the disease has often been reported in the literature [8, 12]. As noted by other authors, patients with spinal TB were of lower social class [8, 13], and many of them did not present earlier with signs of pulmonary TB [10].…”
Section: Discussionsupporting
confidence: 87%
“…However, the total absence of an inflammatory syndrome does not exclude the diagnosis of spinal TB since 12 to 50% of patients may have no biological signs of inflammation [15]. Half of our patients had neurological complications, similar to the reports from other authors, i.e., 20 to 50% [7, 8, 16]. The neurological deficit depends on the extension of the infectious process, compression, and epidural extension [17].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations